Mikhail Gorbachev - Langley, Andrew (Chicago, Ill. Heinemann Library, 2003)
Describes the life and political career of Mikhail Gorbachev and his legacy in the context of the demise of the Soviet Union and conditions in Russia today.
Age Group: Adult
The coup -- Child of the steppe -- Moscow student -- Back to Stavropol -- Looking for patrons -- Party boss -- In the Politburo -- Soviet leader -- Glasnost and perestroika -- The iron curtain disappears -- End of an empire -- Bowing out -- Gorbachev's legacy.
Includes bibliographical references (p. 60) and index.
Keywords: Gorbachev, Mikhail Sergeevich, 1931-; Gorbachev, Mikhail Sergeevich, 1931- Juvenile Literature; Heads of State; Heads Of State -- Soviet Union -- Biography -- Juvenile Literature